Process Factors Affecting the Preparation and Characterization of Dutasteride Nanosuspension - Shaimaa N. Abd-Alhammid ,; Rusul Wahhab Kadhum, (Iraqi Journal of Pharmaceutical Sciences, 2025)
Dutasteride, a synthetic compound belonging to the 4-azasteroid class, functions as a selective and competitive inhibitor of both type 1 and type 2 5-alpha-reductase enzymes. It has been approved for the treatment of symptomatic benign prostatic hyperplasia (BPH) in men. It is Categorized within BCS class II due to its limited aqueous solubility. Dutasteride is available only as a soft gelatin capsule, and the oral bioavailability of this dosage form is approximately 60%. This study's main objective was to create and characterize dutasteride nanoparticles that would enhance their solubility and release rate. The approach utilized in the study consisted of generating a nanosuspension through the solvent/antisolvent precipitation method employing different stabilizers at different concentrations. The research investigated how various process factors affected the particle size and PDI of selected dutasteride nanosuspension formulas. The assessment parameters included particle size, polydispersity index, entrapment efficiency (EE), and in-vitro dissolution patterns. These parameters collectively aided in determining the optimized dutasteride nanosuspension formula. The resulting optimized formula, consisting of 0.5% w/v soluplus as a stabilizer and a solvent/antisolvent volume ratio of 1:10, yielded a particle size of 73.24 nm, and a polydispersity index of 0.184. In vitro dissolution studies revealed that the optimized formulation enhanced the dissolution rate of dutasteride significantly compared to pure drug, it displayed complete release of the drug within 15. The most favorable formulation underwent compatibility testing using FTIR, an investigation of surface morphology with a Field Emission Scanning Electron Microscope (FESEM), and an examination of its crystalline structure via XRPD analysis. The outcome demonstrates that the utilization of the solvent anti-solvent method in the production of dutasteride nanoparticles demonstrates its effectiveness in improving the dissolution rate of dutasteride.